Circular movements and time away from the host country - Amelie F. Constant; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2003)
The economic literature has largely overlooked the importance of repeat migration. This paper studies repeat or circular migration as it is manifested by the frequency of exits of migrants living in Germany, and by the number of years being away from the host country using count data models. More than 60% of the guestworker generation currently living in Germany, the largest European immigration country, are indeed repeat migrants. The findings indicate that immigrants from European countries, the less educated, those with weak labor market attachments, the younger and the older people (excluding the middle ages), and the newcomers and the more seasoned are significantly more likely to engage in circular migration and to stay out of Germany for longer. Males exit more frequently than females but do not differ in the time spent out. Those migrants with family in the home country remain out longer but are not more frequently out.
Keywords: F22; J61; J15; 330; repeat migration; circular migration; guestworkers; minorities; Internationale Wanderung; Rückwanderung; Einwanderung; Ausländische Arbeitskräfte; Minderheit; Schätzung; Deutschland